ANALISA EKONOMI PETANI PENGELOLA KARET DI KAWASAN TEMBAWANG KELURAHAN SEBALO KECAMATAN BENGKAYANG - Suraini, Wati; Lumangkun, Augustine; Haryani, Uke Natalina (JURNAL HUTAN LESTARI, 2015)
Rubber farming in the tembawang area is the main livelihood of household of farmer communities. The research took place in tembawang area at Sebalo village Bengkayang subdistrict. The research aim to know the farmer’s income, the efficiency level of farm rubber done by farmers, the percentage contribution of rubber revenue to the household, and to know the influence factors of farmer’s income. The research conducted from April to May 2014. The research used survey method, and samples were taken by purposive sampling. The results shows that the average net income of sap rubber is Rp 12.050.609,-/household/year or Rp 1.004.217,42/household/month. The efficiency level of 3,34 points means that economically the farm rubber is reasonable and give benefit to the farmer. The income contribution of rubber is 51,44% from total income of the household. The regression analyzed from the three variables influences the income from rubbers. The variables are the number of the tembawang areas (X1), the work experience (X2) and the total of rubber trees that tapped (X3). These three variables collectivelly give significant effect to decrease or increase the farmer’s income from sap rubber with Ftest 23,729 > Ftable (α=0,05;100) = 2,70. So the Halt is accepted and coefficient determination (R2) is 0,426. The variable of the number of rubber trees have high correlation with net income in which the Ttest = 6,758 > Ttable (α=0,05;2) = 4,303. While the space area and the work experience have not corelated in which the Ttest are 2,094 and -1,374 respectively. Keywords : Bengkayang, farmers incomes, rubbers, sebalo village, tembawang.